TEKNIK PEMBENIHAN IKAN LELE (CLARIAS GARIEPINUS) DI INSTALASI BALAI BENIH IKAN LINGSAR - YUSRIN YUSRIN; WASTU AYU DIAMAHESA (GANEC SWARA, 2024)
This study examines the hatching and rearing process of catfish (Clarias gariepinus) larvae at the Fish Seed Center (BBI) in Lingsar, West Lombok Regency. Pond preparation, parent selection, spawning, larval rearing, feeding, and water quality monitoring are the main focuses. The research method used is observation, interviews, and literature review. The results indicate that pond preparation includes cleaning, liming, fertilization, and water filling, while parent selection is based on physical criteria and egg maturity. Spawning is done naturally with water quality monitoring being important for egg survival. Larval rearing includes feeding and growth measurement done on a scheduled basis. Water quality is monitored periodically to ensure optimal conditions. Although the percentage of egg hatching is relatively low, catfish larval rearing shows good growth with the appropriate approach.